2018
DOI: 10.1002/mren.201700065
|View full text |Cite
|
Sign up to set email alerts
|

Model‐Based Reactor Design to Control Hyperbranched Polymer Architecture

Abstract: L is the linearly incorporated unit, one of whose two B's has reacted, and D is the dendritic unit in which both B's have already reacted. The reaction rate constant, k T is for the reaction between an A group and a B in the T unit, while k L is for the reaction between an A and a B in the L unit. The reactivity of the second B group can be represented by the reactivity ratio, r = k L /k T . The reaction systems in which the magnitude of r can be controlled from zero to infinity have been reported. [6] The DB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…On the other hand, if one needs looser structure, the core formation should be avoided. The structural control by using the tanks-in-series process was also discussed previously [25].…”
Section: Largest Cluster Of Tri-branched Unitsmentioning
confidence: 99%
“…On the other hand, if one needs looser structure, the core formation should be avoided. The structural control by using the tanks-in-series process was also discussed previously [25].…”
Section: Largest Cluster Of Tri-branched Unitsmentioning
confidence: 99%
“…For the irreversible step polymerization of AB 2 type monomer, which is another method to synthesize the HB polymers, it was found that CSTR leads to much more compact 3D structure with a larger DB for the large‐sized polymers, compared with the corresponding batch polymerization. Although the use of a single CSTR leads to a very broad molecular weight distribution (MWD), it was found that the tanks‐in‐series process with the tank sequence starting from a large tank followed by a number of smaller tanks is suitable to produce compact HB polymers with a sufficient conversion level . The post‐processes to make the MWD narrower were also considered therein.…”
Section: Introductionmentioning
confidence: 99%
“…These disadvantages could be mitigated by using a tanks‐in‐series process, with a large first tank followed by a number of small tanks, or ideally, a CSTR followed by a PFR. The post‐processes, such as removal of monomer and the introduction of multifunctional core molecules that react with the unreacted focal point unit, can make the MWD narrower significantly.…”
Section: Resultsmentioning
confidence: 99%